The Role of Majelis Taklim (Islamic Learning Assembly) in Instilling Religious Moderation Values in the Community - Subowo Dikdayana (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Indonesia’s multicultural society requires religious moderation to maintain harmony and prevent extremism. As a non-formal Islamic educational institution, Majelis Taklim plays a strategic role in fostering moderate religious attitudes and strengthening social cohesion at the grassroots level. Objective: This study aims to analyse the role, strategies, and contributions of Majelis Taklim in instilling religious moderation values within the Griya Sidomulyo community, Pekanbaru City. Method: This research employs a qualitative descriptive approach. Data were collected through in-depth interviews, participatory observation, and documentation involving administrators, preachers, congregants, and community leaders. Data were analysed through reduction, data display, and conclusion drawing, supported by triangulation to ensure validity. Results: The findings indicate that Majelis Taklim actively promotes moderation values through regular religious study sessions, thematic discussions, and social programs such as Jumat Berkah (Friday Charity Program) and Didikan Subuh (Early Morning Religious Education Program). These activities cultivate tolerance, balance, mutual respect, and social solidarity. Supporting factors include active participation, qualified preachers, and strong community engagement, while financial constraints and coordination challenges remain obstacles. Conclusion: Majelis Taklim functions as an effective grassroots institution for cultivating religious moderation and strengthening social harmony in heterogeneous urban communities. Contribution: This study provides empirical evidence of Majelis Taklim’s strategic role as a community-based model for promoting inclusive and moderate Islamic education.